Effect of using a multi-intelligence strategy on acquiring national concepts in the subject of national and civic education among students of basic sixth education in Jordan - Al-Khashashneh, Khaled Muhammad (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at identifying the effect of using a multi-intelligence strategy on acquiring national concepts in the subject of national and civic education among students of basic sixth education in Jordan. The researcher used the semi-experimental approach to identify the effect of using a strategy based on multiple intelligences on acquiring national concepts. The researcher prepared a test to measure national concepts for the study sample, which consisted of (70) students in two groups (control- experimental). The study reached several results, the most important of which is the effect of a strategy based on multiple intelligence in acquiring national concepts in the subject of national and civic education among students of the basic sixth, where the students of the experimental sample outperformed the students of the control sample. The study recommended the necessity of using the teaching strategy based on multiple intelligences in all social education units.
Keywords: multiple intelligences; national concepts; national education textbooks